Process and outcome of prenatal care according to the primary care models: a cohort study - Alves de Oliveira, Renata Leite [UNESP]; Ferrari, Anna Paula [UNESP]; Lima Parada, Cristina Maria Garcia de [UNESP] (Univ Sao Paulo, Escola De Enfermagem De Ribeirao Preto, 2019)
Objective: to evaluate the process and outcome indicators of the prenatal care developed in primary care, comparing traditional care models and the Family Health Strategy. Method: this is a cohort study, conducted with an intentional sample of 273 mothers/babies from the neonatal period and followed up for one year. Donabedian evaluation was adopted and data were discussed based on the Social Determination of Health. The independent variable was the care model. The dependent variables in the process evaluation were related to the quality of prenatal care and to the quality score created and the evaluation of the outcome, to the conditions of birth and the first year of life. The evaluation of the process was performed by estimating the relative risk and the evaluation of the outcome was performed by the Cox Multiple Regression Model. Results: lower income and risk of the low prenatal quality score were identified in the Family Health Units, where there were more puerperium consultation and health education actions. There was no difference in outcome indicators. Conclusion: possibly the best quality of prenatal care was able to minimize negative socioeconomic effects found in family health, so the outcome indicators were similar in both models of the primary care.
Keywords: Prenatal Care; Evaluation of Health Programs and Projects; Primary Health Care; Family Health Strategy; Child Health; Women's Health